2020
DOI: 10.1111/1462-2920.15010
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and potential biogeochemical impacts of viruses in bulk and rhizosphere soils

Abstract: Summary Viruses can affect microbial dynamics, metabolism and biogeochemical cycles in aquatic ecosystems. However, viral diversity and functions in agricultural soils are poorly known, especially in the rhizosphere. We used virome analysis of eight rhizosphere and bulk soils to study viral diversity and potential biogeochemical impacts in an agro‐ecosystem. The order Caudovirales was the predominant viral type in agricultural soils, with Siphoviridae being the most abundant family. Phylogenetic analysis of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
55
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(70 citation statements)
references
References 75 publications
4
55
0
Order By: Relevance
“…In this study, the contigs identified as virus ranged from 21.93 to 75.37%, but the majority (24.63 to 78.07%) of contigs still could not be identified by comparison to the known virosphere (based on the NT database). This phenomenon has been reported previously for viromes in other environments, including soil [ 5 , 10 ], marine [ 17 ], freshwater [ 54 ], etc. These contigs that originate from viruses but do not align to any reference virus sequence have been referred to as “viral dark matter” [ 55 ].…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…In this study, the contigs identified as virus ranged from 21.93 to 75.37%, but the majority (24.63 to 78.07%) of contigs still could not be identified by comparison to the known virosphere (based on the NT database). This phenomenon has been reported previously for viromes in other environments, including soil [ 5 , 10 ], marine [ 17 ], freshwater [ 54 ], etc. These contigs that originate from viruses but do not align to any reference virus sequence have been referred to as “viral dark matter” [ 55 ].…”
Section: Discussionsupporting
confidence: 84%
“…These contigs that originate from viruses but do not align to any reference virus sequence have been referred to as “viral dark matter” [ 55 ]. Only 19.24–29.91% of contigs showed the similarity to known phages, which was far lower than marine [ 17 ], tropical freshwater [ 54 ] and soil [ 5 , 10 ]. In contigs identified as viruses, dominant viral families with relative abundance more than 1% included Myoviridae , Siphoviridae , Podoviridae , Herpesvirales , Ackermannviridae , Mimivirdae and Phycodnaviridae , which mainly belonged to tailed phages ( Myoviridae , Siphoviridae , and Podoviridae ,).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the genomes of globally abundant ocean viruses, more than two hundred viral-encoded AMGs have been identi ed [8], including carbon, nitrogen, sulfur, and P cycle related genes. However, as far as we know, only four types of viral AMGs (trzN [25], phoH [11], RNR [11] and CAZyme [9,26]) have been identi ed in terrestrial ecosystems. Among them, only the phoH gene is presumed to belong to the Pho regulon and to regulate P uptake and metabolism under low-phosphate conditions [27].…”
Section: Introductionmentioning
confidence: 99%
“…However, the rapid development of viral metagenomics and bioinformatics has provided an opportunity to overcome these obstacles [5,6]. In recent years, large amounts of viral genomes, most of which are novel bacteriophages, have been identi ed from a variety of environments, such as marine environments [7,8], freshwater environments [9], hot spring mats [10], rhizosphere soils [11], and mangroves [12]. The ndings of these studies indicated that bacteriophages interacting with their hosts (bacteria and archaea), acted as key partners in multiple ecosystems.…”
Section: Introductionmentioning
confidence: 99%